2019
DOI: 10.1088/1361-6528/ab0ecd
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity in disordered porous nanomembranes

Abstract: We report measurements and Monte Carlo simulations of thermal conductivity of porous 100nm-thick silicon membranes, in which size, shape and position of the pores were varied randomly. Measurements using 2-laser Raman thermometry on both plain membrane and porous membranes revealed more than 10-fold reduction of thermal conductivity compared to bulk silicon and six-fold reduction compared to non-patterned membrane for the sample with 37% filling fraction.Using Monte Carlo solution of the Boltzmann transport eq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…Similar to thin films, the roughness of the surfaces impacts surface scattering, and therefore thermal conductivity . Further experiments confirmed the importance of geometric parameters such as the filling fraction, surface‐to‐volume ratio, or the neck size, but also demonstrated that a further tuning of the thermal conductivity is possible with PnCs with random hole positions, by varying the hole overlap, i.e., the number and relative position of the phonon channels …”
Section: Thermal Transportmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar to thin films, the roughness of the surfaces impacts surface scattering, and therefore thermal conductivity . Further experiments confirmed the importance of geometric parameters such as the filling fraction, surface‐to‐volume ratio, or the neck size, but also demonstrated that a further tuning of the thermal conductivity is possible with PnCs with random hole positions, by varying the hole overlap, i.e., the number and relative position of the phonon channels …”
Section: Thermal Transportmentioning
confidence: 80%
“…In order to fabricate large area membranes a full back‐etching process has to be performed, i.e., both the handle silicon substrate and the SiO 2 layers have to be removed . We have shown that such free‐standing membranes with thickness down to 100 nm can be further used to fabricate both solid–air and solid–solid PnCs using standard EBL process …”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…The high performance exhibited by nanoarrays depends on the high quality of 0D and 1D materials, and scaling up production is challenging. In contrast, random porous structures are easier to obtain, but the morphology of these nanostructures is uncontrollable and therefore has limited improvement in TE performance [ 116 , 117 , 118 ]. The lithographic process is a method to achieve high porosity in a controlled manner, but it is expensive and only suitable for preparing precision devices [ 119 ].…”
Section: Three-dimensional (3d) Te Materialsmentioning
confidence: 99%
“…[17][18][19][20] Interesting results regarding control of thermal transport have further been obtained for thin films, or membranes, in particular, in connection with alteration of the crystalline structure by (nano)pores. [21][22][23][24] Recently the concept of thermal rectification has been discussed for devices where thermal management is crucial. 20,23,25 A detailed knowledge of parameters affecting thermal rectification is the basis of tailoring heat flux in order to control, for example, cooling and energy conversion in nanostructured devices and can eventually lead to the creation of logic devices where phonons are used as information carriers, also called thermal diodes.…”
Section: Introductionmentioning
confidence: 99%
“…17–20 Interesting results regarding control of thermal transport have further been obtained for thin films, or membranes, in particular, in connection with alteration of the crystalline structure by (nano)pores. 21–24…”
Section: Introductionmentioning
confidence: 99%